Type 2 diabetes is associated with increased risk of dementia, but not mild cognitive impairment: a cross-sectional study among the elderly in Chinese communities - Liu, Guojun; Li, Yong; Xu, Yuzhen; Li, Wei (Frontiers in Aging Neuroscience, 2022)
Background: Previous studies have confirmed that diabetes is associated with cognitive impairment, but there is little data on this among older Chinese. Methods: This study included 192 dementia patients, 610 patients with mild cognitive impairment (MCI), and 2,218 normal controls. Their general demographic information (such as gender, age, education, etc.), disease-related information (hypertension), and diabetes information (such as whether you have diabetes, course of the disease, etc) were collected by standardized questionnaires. The mini-mental state examination (MMSE) and Montreal Cognitive Assessment (MoCA) were used to assess their overall cognitive function, Moreover, 84 healthy, randomly selected older adults also underwent brain MRI scans at the same time, and the target brain regions included the hippocampus, the third, fourth, and fifth ventricles. Results: The proportion of type 2 diabetes was significantly higher in the dementia group (25.5%) than that in the normal elderly group (15.6%) and the MCI group (17.7%). By using stepwise multiple logistics regression analysis, we found that type 2 diabetes was associated with dementia (p = 0.005*, OR = 1.805, 95%CI: 1.199–2.761), but not with MCI (p > 0.05). The volume of the fourth ventricle of the healthy elderly with diabetes was significantly larger than that of the healthy elderly without diabetes (p < 0.05), but there was no statistical difference (p > 0.05) in the volume of the hippocampus, the third ventricle, and the fifth ventricle between the two groups. However, we did not find an association between the fourth ventricle and cognitive scores (MMSE and MoCA). Conclusions: In conclusion, type 2 diabetes in elderly Chinese people is associated with dementia, but not MCI. Type 2 diabetes may impair cognitive function by affecting the volume of the fourth ventricle. However, larger longitudinal follow-up studies are needed to confirm these conclusions.